Development of Islamic Family Law Thought Regarding Legal Norms of Waris, Wasiat and Hibah. - Irfan Abdurahman; Asep Lukman Daris Salam; Erfan Shofari Sholahuddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Discussion of shari'ah which is a reference to divine decrees as